Effect of herpes zoster vaccine on patients after hematopoietic stem cell transplantation: a systematic review and meta-analysis - Xunyi Jiao; Jinli Zhu; Yangyang Ding; Meng Xiao; Zhimin Zhai (Virology Journal)
Abstract Background Herpes zoster(HZ), a severe complication following hematopoietic stem cell transplantation (HSCT), is associated with significant morbidity. The effect of herpes zoster vaccine(HZV) for preventing HZ on patients after HSCT is unclear. We conducted a systematic review and meta-analysis investigating the efficacy and safety of HZV in HSCT recipients. Methods The databases Pubmed, Embase, and Cochrane Library were searched to identify relevant studies. Random-effects models were used to calculate risk ratios (RRs) and 95% confidence intervals (CIs) for HZ infection and related events. Results A total of 3048 individuals from five studies (four randomized controlled trials and one retrospective cohort study) were included. The overall incidence of HZ in the HZV group and control group was 6.4% and 18.3% respectively, resulting in a pooled RR of 0.36 (95%CI, 0.29–0.45; P < 0.001), indicating no heterogeneity (P = 0.88,I 2  = 0). HZV demonstrated a reduction in the risk of PHN (RR, 0.40; 95% CI, 0.15–1.11), although statistical significance was not reached (P = 0.08). Furthermore, through two independent RCTs, HZV showed a decrease in the incidence of HZ-related complications compared to placebo administration. The overall incidence of adverse events in the HZV group and control group was found to be 63.6% and 60.2% respectively, with a pooled RR of 1.02 (95% CI, 0.97–1.06, P = 0.51), indicating no heterogeneity (P = 0.66, I 2  = 0). Conclusion The HZV group demonstrated a significant reduction in the risk of HZ among HSCT recipients, without an increase in adverse events. This highlights the positive impact of HZV on decreasing the incidence of PHN and complications associated with HZ. Furthermore, our findings support the effectiveness and tolerability of HZV as a preventive measure against HZ for HSCT recipients.